Heat Transfer and Friction in a Low-Aspect-Ratio Rectangular Channel with Staggered Slit-Ribbed Walls - Jenn-Jiang Hwang; Tong-Miin Liou (International Journal of Rotating Machinery)
Fully developed heat transfer and friction in a rectangular channel with slit-ribbed walls are examined experimentally. The slit ribs are transversely arranged on the bottom and top channel walls in a staggered manner. Effects of rib open-area ratio (β= 24%, 37%, and 46%), rib pitch-to-height ratio (Pi/H=10,15and20), and Reynolds number (10,000≤Re≤50,000) are examined. The rib height-to-channel hydraulic diameter ratio is fixed at H/De=0.081. It is disclosed that the heat transfer coefficient for the slit-ribbed channel is higher than that for the solid-ribbed channel, and increases with rib open-area ratio. Results also show that the friction factor for the slit-ribbed channel is significantly lower than that for the solid-ribbed one. Moreover, the ribs with larger open-area ratios in a higher flow Reynolds number condition could give the better thermal performance under the constant friction power constraint. Roughness functions for friction and heat transfer are further developed in terms of rib and flow parameters.